2021
DOI: 10.1038/s41467-021-27407-0
|View full text |Cite|
|
Sign up to set email alerts
|

Strategies to package recombinant Adeno-Associated Virus expressing the N-terminal gasdermin domain for tumor treatment

Abstract: Pyroptosis induced by the N-terminal gasdermin domain (GSDMNT) holds great potential for anti-tumor therapy. However, due to the extreme cytoxicity of GSDMNT, it is challenging to efficiently produce and deliver GSDMNT into tumor cells. Here, we report the development of two strategies to package recombinant adeno-associated virus (rAAV) expressing GSDMNT: 1) drive the expression of GSDMNT by a mammal specific promoter and package the virus in Sf9 insect cells to avoid its expression; 2) co-infect rAAV-Cre to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…In addition to approved drugs repurposing and new drugs development, Lu et al reported a novel strategy to package recombinant adeno-associated virus (rAAV) expressing GSDMD-N. They have successfully delivered GSDMD-N into tumor cells and demonstrated pyroptosis induced by these rAAVs in preclinical cancer models including glioblastoma [ 72 ], which can provide enlightenment for the idea of anti-tumor therapy. Till now, a growing body of research has posted attention on GBM.…”
Section: Overview Of Pyroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to approved drugs repurposing and new drugs development, Lu et al reported a novel strategy to package recombinant adeno-associated virus (rAAV) expressing GSDMD-N. They have successfully delivered GSDMD-N into tumor cells and demonstrated pyroptosis induced by these rAAVs in preclinical cancer models including glioblastoma [ 72 ], which can provide enlightenment for the idea of anti-tumor therapy. Till now, a growing body of research has posted attention on GBM.…”
Section: Overview Of Pyroptosismentioning
confidence: 99%
“…A new synthesized ligand TFBIP and its three iridium (III) complexes were found to induce GSDME-mediated pyroptosis, thus decreasing cell viability in several cancers [ 70 ]. MiR-214 targeting caspase-1 or GSDMD-N packaged in rAAVs can both induce pyroptosis in brain tumor cells [ 71 , 72 ]. The reagent consisting of BRAF inhibitors and MEK inhibitors (BRAFi/MEKi) is used to treat BRAF V600E/K−mutant melanoma with FDA approval.…”
Section: Overview Of Pyroptosismentioning
confidence: 99%
“…Pre-clinical GSDM-targeted therapies for cancer are also an emerging area of research. While apoptotic pathways are often disabled in cancer cells, the caspase-8-caspase-3-GSDME axis leading to pyroptosis may be operative (91): aiming to exploit this, Lu et al showed that intratumoral delivery of adenoassociated virus expressing the N-terminal domain of GSDME induced pyroptosis in glioblastoma and breast cancer cells, leading to tumor regression and prolonged survival in preclinical cancer models (92), but this has yet to be tested in humans. Some conventional chemotherapeutic drugs, such as cisplatin and doxorubicin, also cause pyroptosis in cancer cell lines by activating the caspase-3-GSDME pathway (12,93); while micro-RNA-mediated reactivation of GSMDE expression, in combination with cetuximab, effectively induced pyroptosis of tumor cells and reduced tumor volume in a mouse model of aggressive triple-negative breast cancer (17).…”
Section: Therapeutic Targeting Of Gsdmsmentioning
confidence: 99%
“…For example, CAR-T cells may attack not only tumor but also normal cells, resulting in “on-target off-tumor” toxicity ( 19 ). Second, due to the immunosuppressive microenvironment of solid tumors, some immune cells or cytokines infused intravenously cannot successfully reach the tumor site, resulting in immunotherapy being effective in hematological tumors, but still unable to overcome solid tumors ( 20 ). Nanomedicines can overcome some of the shortcomings of simple immunotherapy and enhance the effect of tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%